(untitled) (Ustozlar uchun, 2026)
This scientific article explores the significant role of technology in modern language learning and teaching. It discusses how digital tools, online platforms, and artificial intelligence contribute to improving linguistic competence, learner motivation, and communication skills. The research highlights that technology enhances accessibility, interactivity, and personalization in the educational process, enabling learners to study languages beyond traditional classroom settings. Furthermore, it examines various forms of technological integration, including virtual classrooms, mobile-assisted learning, and multimedia-based instruction. The study also analyzes the pedagogical implications of technology use, emphasizing the necessity of teacher guidance and digital literacy. The findings indicate that when used effectively, technology supports independent learning, fosters global communication, and bridges cultural gaps among learners.